Development of a Low-cost Explosive Vapor Detector Using Metal Oxide Gas Sensors - Ratchapakorn, Natchanon; Ariyakul, Yossiri (My University, 2018)
This paper reports on the development of a low-cost electronics nose for explosive detection. The device is composed of an array of metal oxide gas sensors installed in a 3D printer-made sensor cell. The processor and control circuit were implemented on an FPGA. The proposed device is compact, low power, and low cost. Even though, the concentration of the vapors of explosive materials are at sub-part-per million, the capabilities to sense and identify eight explosive materials; trinitrotoluene (TNT), pentaerythritol tetranitrate (PETN), cyclotrimethylenetrinitramine (RDX), ammonium nitrate, urea powder, dynamite, black powder, and double-base propellant in an open-air environment were confirmed. The reproducibility of the proposed device was also verified.
Keywords: electronic nose; explosive detector; FPGA; metal oxide gas sensor